Analisis Perilaku Pemilih California Dalam Pemilihan Presiden Amerika Serikat Tahun 2020 - Fiorenza, Rima Deana; Erviantono, Tedi; Apriani, Kadek Dwita (Jurnal Nawala Politika; Vol 2 No 1 (2023): Jurnal Ilmu Politik, 2023)
This research examines the behavior of voters in California in the 2020 United States Presidential Election. This analysis will then try to understand American Voters in making the final decision so that they can determine their choice and give voting rights to one candidate. California is the area of the US that has the most electors, namely 55 electors, which is caused by its population density. With this, the voting behavior of California residents has a considerable influence in determining the electoral college's victory. This behavior of US voters tends to hold one-way beliefs. Sets its vote on one representative from a party. Factors from this sociological approach play a major role in voters in the US, both due to environmental, family, and psychological factors of the voters. In addition, voters in America can also be influenced by personal interests which weigh the advantages and disadvantages of individual voters' decisions. Keywords: Voting Behavior, California, Rational Choice, American Voters.